2016
DOI: 10.1038/onc.2016.101
|View full text |Cite
|
Sign up to set email alerts
|

Osteocytic connexin hemichannels suppress breast cancer growth and bone metastasis

Abstract: Although the skeleton is one of predominant sites for breast cancer metastasis, why breast cancer cells often become dormant after homing to bone is not well understood. Here, we reported an intrinsic self-defense mechanism of bone cells against breast cancer cells: a critical role of connexin (Cx) 43 hemichannels in osteocytes in the suppression of breast cancer bone metastasis. Cx43 hemichannels allow passage of small molecules between the intracellular and extracellular environments. The treatment of bispho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 70 publications
(108 reference statements)
3
77
2
Order By: Relevance
“…ATP release and modulation of Ca 2+ concentrations regulate cell proliferation in a variety of cell types 154-156 , and inappropriate hemichannel opening may underlie some hyperproliferative disorders such as hidrotic ectodermal dysplasia 157 . Hemichannel functions have also been linked to vascular disruption and haemorrhage within tumours 158 , and recently Cx43 hemichannels of osteocytes are involved in suppression of breast cancer cell growth and bone metastasis 159 . However, the link between hemichannels and cancer is difficult to conclusively establish as most reagents that block gap junction channels also block connexin hemichannels making assignment of functional consequences specifically to hemichannel functions problematic 160 .…”
Section: Reassessing Connexins In Cancermentioning
confidence: 99%
“…ATP release and modulation of Ca 2+ concentrations regulate cell proliferation in a variety of cell types 154-156 , and inappropriate hemichannel opening may underlie some hyperproliferative disorders such as hidrotic ectodermal dysplasia 157 . Hemichannel functions have also been linked to vascular disruption and haemorrhage within tumours 158 , and recently Cx43 hemichannels of osteocytes are involved in suppression of breast cancer cell growth and bone metastasis 159 . However, the link between hemichannels and cancer is difficult to conclusively establish as most reagents that block gap junction channels also block connexin hemichannels making assignment of functional consequences specifically to hemichannel functions problematic 160 .…”
Section: Reassessing Connexins In Cancermentioning
confidence: 99%
“…Numerous studies have revealed the significant role of GJs in tumors, since recovered expression of connexin that forms GJs or recovered function of GJs could reduce the cell malignant phenotype (11,34,35). The expression of connexin and its derived homotypic GJ suppressed the invasion of tumor cells (36,37).…”
Section: A B Discussionmentioning
confidence: 99%
“…Conditioned media from MLO‐Y4 osteocyte cells treated with bisphosphonates reduced the growth, migration, and invasion of MDA‐MB‐231 human breast cancer cells . These inhibitory effects appear to be mediated by Cx43, as mice with impaired Cx43 gap junctions showed significantly increased tumor burden and an attenuation of the inhibitory effect of bisphosphonates on tumor growth . This study suggests a role of osteocytes and Cx43 hemichannels in the response to bisphosphonates and identifies Cx43 as a novel therapeutic target.…”
Section: Osteocytes and Their Derived Factors As Targets For The Treamentioning
confidence: 69%
“…The beneficial effects of bisphosphonates on the skeleton are also due to the prevention of osteoblast and osteocyte apoptosis, an effect that depends on the regulation of Connexin 43 (Cx43) signaling between neighboring cells . Conditioned media from MLO‐Y4 osteocyte cells treated with bisphosphonates reduced the growth, migration, and invasion of MDA‐MB‐231 human breast cancer cells . These inhibitory effects appear to be mediated by Cx43, as mice with impaired Cx43 gap junctions showed significantly increased tumor burden and an attenuation of the inhibitory effect of bisphosphonates on tumor growth .…”
Section: Osteocytes and Their Derived Factors As Targets For The Treamentioning
confidence: 99%